How bioinformatics enables livestock applied sciences in the genomic era - Garcia, José Fernando [UNESP]; Do Carmo, Adriana Santana [UNESP]; Utsunomiya, Yuri Tani [UNESP]; De Rezende Neves, Haroldo Henrique [UNESP]; Carvalheiro, Roberto; Van Tassell, Curtis; Sonstegard, Tad Stewart; Da Silva, Marcos Vinicius Gualberto Barbosa (Springer Nature, 2012)
This review paper presents the three main approaches currently used in livestock genomic sciences where the bioinfomatics plays a critical role. They are named as Genomic Selection (GS), Genome Wide Association Study (GWAS) and Signatures of Selection (SS). The subsides for the construction of this article were generated in a current project (started in 2011), so called Zebu Genome Consortium (ZGC), which joins researchers from different institutions and countries, aiming to scientifically explore genomic information of Bos taurus indicus cattle breeds and deliver useful information to breeders and academic community, specially from the tropical regions of the world. © 2012 Springer-Verlag.
Keywords: Bos taurus indicus; Genome Wide Association Study; Genomic Selection; Livestock; Signatures of Selection; Tropical Environment; Bos taurus; Genome-wide association; Tropical environments; Agriculture; Genes; Bioinformatics